Renal salvage using stent graft placement after acute renal artery occlusion with prolonged ischemic time. (August 2020) - Gao, Yue; Miserlis, Dimitrios; Longo, G Matthew; Garg, Nitin
Purpose: To describe a patient with acute renal artery occlusion who underwent successful revascularization procedure after experiencing a protracted ischemic period, which resulted in successful retrieval of renal function. Case report: A 58-year-old male with a history of left renal artery stenosis and stent graft placement presented with symptoms of chest pain, shortness of breath, and flank pain. The patient was admitted to the Intensive Care Unit with the diagnosis of multiorgan failure and subsequent anuria that led to the initiation of hemodialysis. Computed tomography angiography demonstrated an aortic occlusion along with bilateral proximal renal artery occlusion with reconstitution of the mid to distal renal arteries via collateralization. The patient underwent angioplasty with bilateral renal artery stent-graft placement and successful revascularization of proximal renal arteries. Post-operatively, his renal function and urine output improved, and the patient was able to be weaned off hemodialysis along with the benefit of concurrent amelioration of his renovascular hypertension. Conclusion: For select patients with renal artery occlusion, revascularization of the renal arteries may result in dialysis independence and stabilization of renovascular hypertension, despite prolonged time of ischemia.